Second supplement to the food chemical codex (National Academy of Sciences, 1975)
The proyect that is the subject of this report was approved by the Governing board of the National Research Council, acting in behalf of the National Academy Sciences. Such approval reflects to Board's judgment that the project is of national importance and appropriate with respect to both the purposes and resources of the National Research Council.